The Downside of Preclusion: Some Behavioural and Economic Effects of Cause of Action Estoppel in Civil Actions - Sinai, Yuval (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2011)
The primary objective of the present article is to draw attention to the drawbacks of preclusion, especially of the rules of cause of action estoppel. The article challenges the traditional assumption that the rule of cause of action estoppel increases efficiency by introducing some economic and behavioural effects of the rule, especially the effects of the rule against splitting a single claim or cause of action.Analysis of the effects of cause of action estoppel has three major methodological goals: (a) to re-examine the rule in light of the behaviour modification model, (b) to evaluate the economic efficiency of the rule and its effect on the cost of litigation, and (c) to consider the influence of the rule on the chances of reaching a settlement.The article discusses the problematic incentives of litigating parties under the current Anglo-American rule of cause of action estoppel, and some of its harmful effects on the conduct and cost of litigation as well as on the chances of reaching a settlement. The article shows that, in many cases, the cause of action estoppel rules have undesirable effects on the conduct of litigation, including stimulating overlitigation in the initial action. Furthermore, the rule against splitting a single cause of action does not always contribute to an economically efficient legal system, and reduces the chances of reaching a settlement, which has a harmful effect on both the economic and behavioural aspects of litigation. By contrast, allowing the splitting of a single cause of action can significantly increase the litigants’ incentives to settle, providing the parties with opportunities for employing useful settlement strategies.